2016
DOI: 10.5812/archcid.39666
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Human Papilloma Virus Type 16 in Epithelial Ovarian Tumors Samples

Abstract: Background: Ovarian carcinoma is the most common malignancy in women and is a cancer with a 15% -50% prevalence in the world. Human papilloma virus (HPV) is considered a factor in cervical and ovarian cancer (OCa) and is related to squamous cell carcinoma in the cervical region. The effect of fixed infection may cause chronic inflammation, in the cancer of ovaries it has received very rare attention, although a background of pelvic inflammatory disease (PID) in a case-control study is associated with a higher … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 21 publications
1
11
0
Order By: Relevance
“…The results of present study showed that the frequency of HPV infection in malignant tumor groups was significantly higher than benign and the control groups. In agreement with our results, Dadashi et al reported that the frequency of HPV in malignant ovarian tissue was significantly higher than the tissues from benign participants (13) . Moreover, Al-Shabanah et al reported that 42% and 8% of the ovarian carcinoma samples and normal adjacent tissues as the control group had positive result for HPV, which was statistically IRANIAN JOURNAL OF PATHOLOGY significant (22).…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…The results of present study showed that the frequency of HPV infection in malignant tumor groups was significantly higher than benign and the control groups. In agreement with our results, Dadashi et al reported that the frequency of HPV in malignant ovarian tissue was significantly higher than the tissues from benign participants (13) . Moreover, Al-Shabanah et al reported that 42% and 8% of the ovarian carcinoma samples and normal adjacent tissues as the control group had positive result for HPV, which was statistically IRANIAN JOURNAL OF PATHOLOGY significant (22).…”
Section: Discussionsupporting
confidence: 94%
“…Although the association of HPV with cervical cancer is well defined (8), the role of HPV in other cancers, such as esophageal squamous cell carcinoma, lung, prostate, breast, skin, colorectal, urinary tract and ovarian cancers has not been proven conclusively (9)(10)(11) . In this regards, (13) . EBV is the first human virus to be assigned as carcinogenic pathogen .…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…The majority of cervical cancer is mediated by HPV16 and HPV18 encoding the E6 and E7 oncoproteins. 50,51 There is a close relationship between HPV infection and the TGF-β pathway in cervical tissues; investigations have reported upmodulated TGF-β levels in HPV-positive cervical cancers compared with HPV-negative ones and have suggested a positive correlation between the expression levels of TGF-β and the HPV E6/E7 oncogenes, which may be due to trans-regulatory functions of the E6/E7 oncoproteins, so that, HPV16 E6/E7 have been shown to enhance TGF-β promoter activity by interacting with an Sp1-binding site placed in the TGF-β core promoter. 52 However, a prominent aspect of malignant transformation in cervical epithelial cells is the progressive loss of TGF-β responsiveness.…”
Section: Human Papilloma Virusmentioning
confidence: 99%
“…Human papillomavirus (HPV) is a small virus with doublestranded DNA that is a member of the Papillomaviridae family, namely, a group with a well-recognized etiological role in cervical and vaginal cancer. [1][2][3] There is evidence for the presence of more than 100 types of HPV in the medical literature. In addition, 15 types of HPV (16,18,35,31,39,51,45,56,52,66,59, 69, 68, 82, and 73) are considered to be highly involved in the pathogenesis of genital cancer in women while HPVs responsible for the warts of genitals and skin (HPV 6,11,43,42,40,44,61,54,72,70, and 81) have lower pathogenicity.…”
Section: Introductionmentioning
confidence: 99%